CLINICAL MANIFESTATIONS AND OUTCOMES OF COVID-19 IN THE ELDERLY GROUP: OBSERVATIVE COHORT STUDY - Sholehuddin, Muhammad Afif; Rohman Firmansya, Muhammad Ainul; Rachmat Ilahi, Nila Hapsari; Wahyuni, Kharisma Rizqiah; Kurniati, Kurniati; Ilahi, Wiwik Kurnia; Wesprimawati, Irma; Luthfiyah, Anik (JURNAL KEDOKTERAN, 2022)
Indonesia has the 4th largest number of elderly population in the world. Recent studies, had shown that elderly population was associated by higher risk for developing severe infection and worse outcome compared to general population. While growing number of evidence support those finding, few local study had shown similar result. This study was aimed to describe clinical manifestation and outcome of COVID-19 in elderly population. This Observational Cohort studies was conducted on subject admitted on Gelora Joko Samudro observation hut, Gresik for COVID-19 with mild or no symptoms (based on clinical symptom classification of COVID-19 infection of Indonesian Ministry for Health, 5th Revision July 2020) and age over 60 years old. Subjects aged 20-59 were enrolled as paired control group. From total 1238 patient, there are 24 (1.94%) subjects aged more than 60. Majority of the subject were male (75%), with average age 64.7±4.78 years old. Compared to the control group, elderly had lower incidence of symptomatic infection (HR 0.4 CI95% 0.16-0.77), lower incidence of negative conversion (HR 0.1 CI95% 0.03-0.30), longer duration of viral shedding (MD 3.8 CI95% 1.73-5.77) and longer day of inpatient (MD 4.1 CI95% 2.56-5.61). In conclusion, elderly population had lower incidence of symptomatic infection but had worse clinical outcome in negative conversion, duration of viral shedding and day of hospitalization. Keywords: Elderly; COVID-19; Clinical Manifestation; Clinical Outcome.